Vean tradition as a local wisdom of customary people and its relevance to maritime history learning - Agustinus Ufie; Jenny K Matitaputy; Jeanet Kufla (Journal of Education and Learning (EduLearn), 2020)
Vean is a tool used to catch fish in traditional way in Ohoi Disuk, Kei Island, in Southeast Maluku. This study aims to examine vean tradition as a local wisdom of customary people that has been inherited from generation to generation. This research uses qualitative method applying descriptive analytical approach. The number of respondents is 10 people. The results show that the construction of vean resembles the human body, which implies that humans must move their limbs to work in order to meet the life needs. In addition, vean (sero) can also build relationship between the sea and humans as keepers and connoisseurs of nature. Vean has three main motivations, namely economic aspect to create quality of life, social aspect to develop a sense of justice without expecting anything in return, and ecological aspect for the conservation of ecosystems and marine life. On the other hand, vean has very meaningful values to maintain kinship and brotherhood in building social relations, creating a good social harmony. Based on the perspective, motivation, and values contained in vean, this local wisdom can be used as a way to strengthen maritime culture in history learning because it comes from the culture of local community as a source of learning.